GPR System Performance Compliance According to COST Action TU 1208 Guidelines - Pajewski, Lara; Vrtunski, Milan; Bugarinovic, Željko; Ristic, Aleksandar; Govedarica, Miro; Van Der Wielen, Audrey; Gregoire, Colette; Van Geem, Carl; Derobert, Xavier; Borecký, Vladislav; Salih Serkan, Artagan; Fontul, Simona; et al. (My University, 2018)
Ground Penetrating Radar (GPR) systems shall be periodically calibrated and their performance verified, in accordance with the recommendations and specifications of the manufacturer. Nevertheless, most GPR owners in Europe employ their instrumentation for years without ever having it checked by the manufacturer, unless major flaws or problems become evident, according to the results of a survey carried out in the context of COST (European Cooperation in Science and Technology) Action TU1208 “Civil engineering applications of Ground Penetrating Radar.” The D6087–08 standard, emitted by the American Society for Testing Materials (ASTM International), describes four procedures for the calibration of GPR systems equipped with air-coupled antennas. After a critical analysis of those procedures, four improved tests were proposed by a team of Members of the COST Action TU1208, which can be carried out to evaluate the signal-to-noise ratio, short-term stability, linearity in the time axis, and long-term stability of the GPR signal. This paper includes a full description of the proposed tests and presents the results obtained by scientists from Belgium, Czech Republic, Portugal, and Serbia, who executed the tests on their GPR systems. Overall, five pulsed control units and nine antennas were tested (five horn and four ground-coupled antennas, with central frequencies from 400 MHz to 1.8 GHz). While the performed measurements are not representative enough to establish absolute thresholds for the tests, they provide a valuable indication about values that one could obtain when testing GPR equipment, if the equipment is working reasonably well. Moreover, by periodically repeating the tests on the same equipment, it is possible to detect any significant shift from previously obtained values, which may imply that the GPR unit or antenna under test is not working in a normal or satisfactory manner. We also believe that executing the tests described in this paper is a useful exercise to gain awareness about the behaviour of a GPR system, its accuracy and limits, and how to best utilize it.
Keywords: Ground Penetrating Radar (GPR); antennas; calibration; system performance compliance; signal-to-noise ratio; signal stability; signal linearity in the time axis